Penggunaan Tutur di Kalangan Remaja Suku Jawa dalam Berkomunikasi di Desa Pelita Jaya Kecamatan Belitang Madang Raya Kabupaten OKU Timur Tahun 1984-2019 - Novilia Dwipayana; Syaiful Syaiful; Sumargono Sumargono (Journal of Social Science Education, 2021)
The Javanese are one of the oldest ethnic groups in Indonesia. The Javanese have identical cultural characteristics, namely the traditions, behavior, and life attitudes of the Javanese people. The Javanese in communicating use the Javanese language. In everyday communication, the Javanese language has begun to be abandoned by its speakers. This study aims to find out the factors of changes in speech use among Javanese youth in communicating in Pelita Jaya Village, Belitang Madang Raya District, East OKU Regency in 1984-2019. The method in this study is a descriptive method with qualitative data analysis techniques, namely research that is described in words, facts about changes in speech use among Javanese youth in communicating in Pelita Jaya village, Belitang Madang Raya district, East OKU district. Data collection techniques through interviews, observation, documentation. The results of research on changes in speech use among Javanese youth in communicating in Pelita Jaya Village, Belitang Madang Raya District, East OKU Regency in 1984-2019 are several factors that influence the change in speech itself caused by factors, namely: self-factor , family factors, environmental factors, changing times, education factors. Keywords: Change Factors, Speech, Youth, Communication Suku Jawa merupakan salah satu suku paling tua di Indonesia. Suku Jawa mempunyai ciri khas kebudayaan yang identik yaitu tradisi, perilaku, serta sikap hidup dari masyarakat Jawa. Suku Jawa dalam berkomunikasi menggunakan bahasa Jawa. Dalam komunikasi sehari-hari, bahasa Jawa sudah mulai ditinggalkan oleh para penuturnya. Penelitian ini bertujuan untuk mengetahui faktor-faktor perubahan penggunaan tutur dikalangan remaja suku jawa dalam berkomunikasi di Desa Pelita Jaya, Kecamatan Belitang Madang Raya, Kabupaten OKU Timur tahun 1984-2019. Metode dalam penelitian ini adalah metode deskriptif dengan teknik analisis data kulitatif yaitu penelitian yang diuraikan dengan kata kata, fakta mengenai perubahan penggunaan tutur dikalangan remaja suku jawa dalam berkomunikasi di desa Pelita Jaya, Kecamatan Belitang Madang Raya, Kabupaten OKU Timur. Teknik pengumpulan data melalui wawancara, observasi, domunentasi. Hasil penelitian mengenai perubahan penggunaan tutur dikalangan remaja suku jawa dalam berkomunikasi di Desa Pelita Jaya, Kecamatan Belitang Madang Raya, Kabupaten OKU Timur tahun 1984-2019 adalah adanya beberapa faktor yang mempengaruhi perubahan turur itu sendiri yang disebabkan oleh faktor-faktor yaitu : faktor diri sendiri, faktor keluarga, faktor lingkungan, faktor perubahan zaman, faktor pendidikan. Kata Kunci: Faktor-faktor Perubahan, Tutur, Remaja, Komunikasi